Impact of Relationship Breakdown, Including Abuse and Negotiation of Co-Parenting Arrangements, on Fathers’ Mental Health, Help-Seeking, and Coping - Benjamin Hine; Eilish Mairi Roy; Ching-Yu Huang; Elizabeth Bates (Social Sciences)
Background: This study explores the impact of family breakdown, separation, post-separation abuse, and negotiating of co-parenting arrangements on fathers’ physical and mental health, as well as their coping mechanisms and experiences of support, both informal and formal. Methods: Using data from a survey of 141 fathers and interviews with 30 participants, we examined the impact of family breakdown on fathers and their children and how they coped and were supported. The data were analysed using reflexive thematic analysis to identify key themes. Results: Findings highlighted four primary themes: the impact on fathers, the impact on children, fathers’ strategies for coping, and fathers’ experience of formal and informal support. Conclusions: The results indicate that fathers need greater support mechanisms post-separation, in ways that specifically appreciate their unique experiences as men and fathers.